A New Painting of Calypso in Pliny the Elder - Anthony Corbeill (Eugesta, 2017)
At Naturalis Historia 35.147, Pliny offers precious information on female artists of Greece and Rome. This article emends Pliny’s text, thereby attributing a more precise subject to a painting by a Greek woman. Linderski has discussed the difficulties associated with text and interpretation of the first sentence of 35.147 (ZPE 2003.83-87). Pliny lists female painters from antiquity, including Irene, daughter of Cratinus (text of Mayhoff 1897): Irene, Cratini pictoris filia et discipula, puellam, quae est Eleusine, Calypso, senem et praestigiatorem Theodorum, Alcisthenen saltatorem (sc. pinxit). Since the nineteenth century, scholars have debated whether Calypso is here in the accusative or nominative case; in other words, was she one of the known works of Irene or does Pliny include an unattested painter named Calypso? Linderski ingeniously reconstructed how ancient uncertainty over the form Calypso had corrupted the text. An overly meticulous scribe glossed Calypso with the more common accusative in late antiquity, Calypsonem. This form was subsequently incorporated into the text and miscorrected to Calypso senem. Linderski therefore proposed deleting senem and reading Calypso as accusative, the accusative form that we know Pliny preferred (Char. gramm. p. 162.6-11). While agreeing that Calypso is a painting, I propose here an emendation that is more plausible paleographically and accords well with known representations of the nymph. These fall into two main types: standing beside Odysseus at his raft (three examples) or seated alone (two examples, one of which is attested at Plin. nat. 35.132). I read Calypso sedentem for the transmitted text (Calypso senem et) and then discuss five points that favor this emendation. I close by conjecturing how Irene’s “new” subject – a Calypso seated, presumably after the departure of Odysseus – can supplement our appreciation of women artists of Greece and Rome.